Peran Psikoedukasi Kepercayaan Diri Untuk Meningkatkan Pengetahuan Pencegahan Bullying Pada Anak Panti Asuhan: The Role of Psychoeducation on Self-Confidence to Enhance Knowledge of Bullying Prevention among Orphanage Children - RISA WULAN MEI ASTUTI; Effy Wardati Maryam (Academia Open, 2025)
General Background: Bullying is a repetitive aggressive behavior that generates serious physical, emotional, and psychological consequences among vulnerable children. Specific Background: Children living in orphanages are particularly at risk due to limited supervision and imbalanced caregiver–child ratios, which may contribute to insufficient understanding of bullying prevention and reduced self-confidence. Knowledge Gap: Despite growing concern regarding bullying in institutional care settings, structured psychoeducational programs targeting self-confidence and bullying prevention knowledge among orphanage children remain limited. Aims: This study aimed to examine changes in bullying-related knowledge after a psychoeducational intervention focused on strengthening self-confidence among orphanage children. Results: Using a quantitative pre-experimental one-group pretest–posttest design involving 38 participants, statistical analysis with the Wilcoxon signed-rank test revealed a significant difference between pretest and posttest scores (p < .001), with mean scores increasing from 9.842 to 11.474. Novelty: This study provides empirical evidence of structured psychoeducation delivered within an orphanage setting using a controlled pre–post assessment framework. Implications: The findings support the integration of psychoeducational programs as an initial preventive strategy to foster awareness, strengthen self-confidence, and promote safer social environments in institutional childcare contexts. Keywords: Psychoeducation, Bullying Prevention, Self Confidence, Orphanage Children, Pre-Experimental Design Key Findings Highlights: Significant score difference observed between pretest and posttest assessment Statistical testing confirmed non-normal distribution requiring Wilcoxon analysis Knowledge gains demonstrated measurable change after structured intervention